The development and application of a comprehensive land degradation assessment method in the Monduli District, Tanzania - Kiunsi, Robert Benjamin (Department of Environmental and Geographical Science, 2023)
Land degradation in drylands, remains a highly contentious issue. Broadly speaking, land degradation may be defined as undesirable changes in the state of land from productive to unproductive due to natural or human made factors